Titanium Surface Roughness Modification Using Ion Beam and Mechanical Method; Surface Modification of Materials by Ion Beams (SMMIB-2019) - Tarbokov V. A. Vladislav Aleksandrovich; Remnev G. E. Gennady Efimovich; Pavlov S. K. Sergey Konstantinovich; Nochovnaya N. A.; Eshkulov V. E. (Biomedical and Industrial Applications. Poster Session, 2019)
Заглавие с экрана